The Study of Relationships Between Street Vendors and Spatial Characteristics of Urban Area: A Case Study of Ramkhamhaeng Area, Bangkok - Premphunsawad, Nuttapong; Pokharatsiri, Jaturong (Journal of Architectural/Planning Research and Studies (JARS), 2018)
The objectives of this research are to study the relationships between spatial characteristics of urban area and behaviors of street vendors. The studied case of this research paper is Ramkamhaeng area in Hua Mak, Bangkapi, Bangkok. By using systematic observation as the main data collection method, the researcher applied the GIS software, using Spatial Analysis and Geoprocessing methods, as a tool to analyse the relationships between the locations and typologies of the street vendors and the following variables: building uses, locations of facilities and large-scale commercial buildings, relevant roads and public transportation modes. The results of the study revealed the distribution of street vendors as affected by all the aforementioned variables. The commercial use was the most significant building use influencing the availability of street vendor products. In particular, clothes and household goods were densely located near the large-scale commercial buildings. The results suggested a realistic interpretation for sustainable street vendors management.